Assessment of handgrip strength in kinesiological evaluation - Vidović, Milica; Aleksic, Aleksandra; Nedovic, Nenad (Education and Research in Health Sciences, 2026)
Handgrip strength is a widely recognized and valid biomarker of muscle strength and overall health status, and it has significant predictive value for various health outcomes. Given its easy application, low cost, and the reliability of measurements obtained using a dynamometer, this parameter has become a frequent topic of scientific research. Studies have consistently shown that decreased handgrip strength correlates with increased mortality, longer hospital stays, and reduced physical functioning. Additionally, grip strength is associated with cognitive functioning, the risk of chronic diseases (such as cardiovascular disease and dementia), as well as a higher likelihood of frailty and sarcopenia. This multidimensional aspect of grip strength and its predictive capability make it an important tool in health assessment, rehabilitation, and the development of training programs in kinesiology practice. The aim of this paper is to explore the possibilities offered by the use of a grip strength dynamometer.